Average Error: 0.0 → 0.0
Time: 7.4s
Precision: 64
$\left(x + a \cdot g\right) + b \cdot g$
$\left(x + a \cdot g\right) + b \cdot g$
\left(x + a \cdot g\right) + b \cdot g
\left(x + a \cdot g\right) + b \cdot g
double f(double x, double a, double g, double b) {
double r2489572 = x;
double r2489573 = a;
double r2489574 = g;
double r2489575 = r2489573 * r2489574;
double r2489576 = r2489572 + r2489575;
double r2489577 = b;
double r2489578 = r2489577 * r2489574;
double r2489579 = r2489576 + r2489578;
return r2489579;
}


double f(double x, double a, double g, double b) {
double r2489580 = x;
double r2489581 = a;
double r2489582 = g;
double r2489583 = r2489581 * r2489582;
double r2489584 = r2489580 + r2489583;
double r2489585 = b;
double r2489586 = r2489585 * r2489582;
double r2489587 = r2489584 + r2489586;
return r2489587;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.0

$\left(x + a \cdot g\right) + b \cdot g$
2. Final simplification0.0

$\leadsto \left(x + a \cdot g\right) + b \cdot g$

# Reproduce

herbie shell --seed 1
(FPCore (x a g b)
:name "x + a * g + b * g"
:precision binary64
(+ (+ x (* a g)) (* b g)))